Deepening the knowledge about dermatosparaxis in Brazilian White Dorper population: Basis for the development and implementation of a genetic disease eradication program in sheep - Nogueira, Joel Fonseca; Borges, Alexandre Secorun [UNESP]; de Andrade, Danilo Giorgi Abranches [UNESP]; Bezerra, Flávia Caroline Moreira; de Oliveira-Filho, José Paes [UNESP]; Cunha, Samla Marques Freire; Gouveia, Gisele Veneroni; Gouveia, João José de Simoni (Elsevier, 2018)
The objectives of this study were to develop a molecular test to identify the dermatosparaxis associated mutation in Brazilian White Dorper sheep and to investigate aspects involved with introduction and dissemination probability of this disease. Partial sequences of the ADAMTS2 gene were used to design a TETRA-ARMS genotyping approach to identify the dermatosparaxis associated mutation. This procedure was validated using 15 samples with known genotypes. After the validation, 19 White Dorper individuals were genotyped with the newly developed test. To deepen the knowledge about the aspects involved with introduction and dissemination probability of dermatosparaxis trough Brazilian White Dorper population, the genotypes and individual identification of 131 individuals used in two independent studies were merged to the 19 newly genotyped individuals and the complete genealogical information was retrieved from the Brazilian Sheep Breeders Association database. The newly developed TETRA-ARMS genotyping approach permitted a perfect match when compared with other methodologies. Observed allele frequency for the dermatosparaxis associated allele was 7.00%. Geneprob Analysis permitted the prediction of 63 individuals as putative wild type homozygotes and 12 as putative heterozygotes. MRCA analysis permitted the identification of seven individuals divided in six clusters. Pedigree analysis indicate that this process was complex because there are, at least, two Australian and four South African lineages carrying the mutated allele that were introduced in Brazil. Finally, it can be highlighted that the development and implementation of a program aiming to eradicate/control the dermatosparaxis associated mutation is needed in Brazil and that the combination of a low cost molecular test and genealogical analysis can be an alternative to reduce genotyping costs and to ensure the effectiveness of the program.
Keywords: Ehlers-Danlos syndrome; Molecular diagnostic; Pedigree analysis; Small ruminants; TETRA-ARMS